RANCANG BANGUN SISTEM PENGOLAHAN DATA PESERTA DIKLAT DI LP3SDM AZRA PALEMBANG - Halim, RM Nasrul (Universitas Bina Darma, 2016)
Data processing system of training participants in LP3SDM AZRA, still use a simple computer application. Data recording process requires a rather long time and also can occur repeatedly writing of participant data (data duplication) caused by the negligence of officials. In the process of data search takes a long time having to search the data training participants in the book. This research aims to building a computerized training participants data processing system in LP3SDM AZRA Palembang. This research uses waterfall model of system development methods.The results obtained of this Research are this data processing system can help the process of inputting the data training participants in LP3SDM AZRA Palembang becomes easier and can simplify the process of data search training participants more quickly and can reduce errors in data entry training participants and can reduce duplication data of participants. Keywords: training, LP3SDM AZRA, data processing